The mystery of the hidden gallbladder: Navigating the unseen - Momin Shakeeb; Romana Riyaz; Sajjad Ahmed Khan; Khadija Fatima; Husna Fatima (Clinical Case Reports, 2024)
Key Clinical Message This case underscores the importance of advanced imaging techniques in diagnosing complex biliary anomalies. Accurate Magnetic Resonance Cholangiopancreatography and ultrasound evaluations can distinguish between choledochal cysts and duplicate gallbladders, guiding effective surgical intervention and improving patient outcomes.